The Integration Of Rectangular SIW Filter and Microstrip Patch Antenna Based On Cascaded Approach - Zakaria, Z; Sam , W. Y; Abd Aziz, M. Z. A; Ismail, M. M (2013)
This paper presents the technique for integrating the rectangular Substrate Integrated Waveguide (SIW) filter with the rectangular microstrip patch antenna to produce filtering and radiating element in a single device. To proof the concept, the integrated microwave filter and antenna at center frequency of 2 GHz was demonstrated and validated through simulation and measurement. It demonstrated promising measured results, which were ingood agreement with the simulated results. The integrated microwave filter and antenna would be beneficial in microwave systems where the reduction of overall volume and weight as well as cost is very important such as in base stations and multiplexer in any communication systems.